1986
DOI: 10.1128/jb.168.2.947-952.1986
|View full text |Cite
|
Sign up to set email alerts
|

Glucose represses formation of delta-(L-alpha-aminoadipyl)-L-cysteinyl-D-valine and isopenicillin N synthase but not penicillin acyltransferase in Penicillium chrysogenum

Abstract: The content of a-aminoadipyl-cysteinyl-valine, the first intermediate of the penicillin biosynthetic pathway, decreased when Penicillium chrysogenum was grown in a high concentration of glucose. Glucose repressed the incorporation of [14C]valine into a-aminoadipyl-cysteinyl-[14C]valine in vivo. The pool of a-aminoadipic acid increased sevenfold in control (lactose-grown) penicillin-producing cultures, coinciding with the phase of rapid penicillin biosynthesis, but this increase was very small in glucose-grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
4
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 23 publications
1
46
4
1
Order By: Relevance
“…These results might also explain the observation that glucose efficiently inhibits penicillin production in P. chrysogenum only when added at an early stage of a batch fermentation (41). Later addition of glucose cannot repress the enzymes already produced, because the specific activity of IPNS is not inhibited by glucose in vitro (42). The expression of acvA, however, appears to be unaffected by glucose.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…These results might also explain the observation that glucose efficiently inhibits penicillin production in P. chrysogenum only when added at an early stage of a batch fermentation (41). Later addition of glucose cannot repress the enzymes already produced, because the specific activity of IPNS is not inhibited by glucose in vitro (42). The expression of acvA, however, appears to be unaffected by glucose.…”
Section: Discussionmentioning
confidence: 49%
“…ACV and IPN are precursors of penicillin, and their synthesis is catalyzed by ACVS and IPNS. Furthermore, the specific activity of IPNS but not of ACT is reduced in cells of a penicillin production strain (AS-P-78) grown on glucose (42). These results suggested that glucose represses the formation of the enzymes ACVS and IPNS in P. chrysogenum (21,41,42).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Production of penicillin, uptake of [I4C]valine and incorporation of ['4C]valine into penicillin were carried out as described previously [19,201. ~7 1 .…”
Section: Experimental Procedures Microorganismsmentioning
confidence: 99%